New palynostratigraphic data of the Irati (Assistência Member) and the Corumbataí formations, Paraná Basin, Brazil, and correlation with other south American basins - Rocha, H.V. (2020)
ABSTRACT: This research presents the palynostratigraphy of organic-rich shales from the Irati and the Corumbataí formations, Paraná Basin (PB), Southeastern Brazil, as part of an unconventional hydrocarbon source rock and CO2 reservoir assessment study. Thirty-four samples from the Corumbataí Formation and the Assistência Member of the Irati Formation were collected in the states of Goiás (northern border of the PB), São Paulo and Paraná (eastern and southern border of the PB, respectively). The acquired data allowed to establish a comprehensive palynostratigraphic study across the basin where a total of 18 pollen genera (34 pollen species), seven spore genera, four microplankton genera (1 species), and Chlorophyceae algae species where identified. The palynostratigraphic analysis also reveals a clear dominance of bisaccate pollen grains such as Corisaccites alutas, Lueckisporites virkkiae, and Weylandites lucifer. The Lueckisporites virkkiae zone was identified in the upper part of the Irati Formation (Assistência Member) and the lowermost part of the Corumbataí Formation, indicating a Kungurian to Roadian age for this part of the succession. Differences in the Guttulapollenites hannonicus and Tornopollenites toreutos biostratigraphic ranges, recovered in the Corumbataí Formation, suggest an earlier development of these species in the Paraná Basin during the middle Permian. Therefore, to evaluate the differences in the first occurrences of key species within the Paraná Basin, a close palynostratigraphic correlation between the main Guadalupian-Lopingian South American Gondwana basins is tentatively established.